The Effects of Gender Integration on Men: Evidence from the U.S. Military - Greenberg, Kyle; Wasserman, Melanie; Weber, E Anna (Quarterly Journal of Economics, 2026)
Abstract Do men negatively respond when women first enter an occupation? We answer this question by studying the end of one of the final explicit occupational barriers to women in the United States: in 2016, the U.S. military opened all positions to women, including historically male-only combat occupations. We exploit the staggered integration of women into combat units to estimate the causal effects of the introduction of female colleagues on men’s job performance, behavior, and perceptions of workplace quality, using monthly administrative personnel records and rich survey responses. We find that integrating women into previously all-male units does not negatively affect men’s performance or behavioral outcomes, including retention, promotions, demotions, separations for misconduct, criminal investigations, and medical conditions. Most of our results are precise enough to rule out small detrimental effects. However, there is a wedge between men’s perceptions and performance. The integration of women causes a negative shift in male soldiers’ perceptions of workplace quality. The decline is driven by units integrated with female officers, likely arising from female officers increasing men’s awareness of workplace problems or from men’s dissatisfaction from working with women in positions of authority—even though men in such units show some performance gains. If male-dominated workplaces are reluctant to incorporate women due to expectations that men will become less productive, our paper provides evidence to weigh against that notion.